An adaptive damage detection method based on differential evolutionary algorithm for beam structures. (June 2021) - Wang, Naige; Jiang, Yongying; Zhong, Yongteng; Shao, Liang
Highlights: Present an adaptive damage detection method for beam structures. Apply BWSI finite element method to model the damaged beam structures. Use DE algorithm to adaptively select the parameters of the proposed method. Abstract: An adaptive singular value decomposition (SVD) method is proposed to detect damage based on the differential evolutionary algorithm for beam structures. B-spline wavelet on the interval finite element method is applied to model the damaged structures. The modal shape data obtained by modal analysis are used to construct attractor trajectory matrix, and SVD-based method is adopted to detect damage locations. In order to accommodate to different damage cases, differential evolutionary algorithm (DE) is used to adaptively optimize the parameters of SVD-based method. Both simulation and experiment researches are set up to verify the proposed method. The results indicate that the presented method is accurately effective to identify the damage for beam structures.